Seroprevalence and risk factors of Hepatitis B and C Virus infection Among Inmates in a Correctional Service, Nasarawa State, Nigeria (Lafia Journal of Scientific and Industrial Research, 2024)
Hepatitis infection has remained a reoccurring public health challenge. The seroprevalence of Hepatitis B and Hepatitis C virus infection among inmates in Lafia correctional service, Nasarawa State, Nigeria was assessed. Blood samples of 120 inmates were screened using the HBV surface antigen (HBsAg) rapid test Dip-strip and HCVAb plus rapid test strip. Socio-demographic and risk factors were analyzed using Fishers exact test binary logistics regression (p ≤ 0.05). Inmates were 29.16 % HBV and 8.3% HCV seropositive. Male inmates were 30% HBV and 8.18% HCV and females were 20% HBV and 10% HCV seropositive. Inmates ≥ 40 years and married inmates are more likely to be infected with HBV and HCV infections. Illicit drug use and incarceration above 5 years were risk factors significant for HBV and HCV prevalence. The high seroprevalence and risk factors of HBV and HCV infections among inmates needs prompt sensitization, screening and vaccination programmes.
Keywords: Hepatitis; correctional service; inmates; risk factors; Seroprevalence